Intensity-dependent near-threshold ionization of Kr in the vacuum-uv. (July 2019) - Varvarezos, Lazaros; John T, Costello; Duesterer, Stefan; Bomme, Cedric; Erk, Benjamin; Hartmann, Gregor; Rompotis, Dimitrios; Manschwetus, Bastian; Savelyev, Evgeny; De Fanis, Alberto; Meyer, Michael; Mazza, Tommaso; et al.
Abstract: In this work, we present measurements of the intensity-dependent photoelectron spectrum of Kr irradiated by the FLASH FEL tuned to a photon energy of 25.8 eV. Intensity dependent photoelectron spectra were obtained with the aid of a Velocity Map Imaging (VMI) spectrometer. As the FEL photon energy is close to threshold, two photon sequential double ionization is favoured. The number of open channels is kept to a minimum and leading to a simple description of the process.